Vietnam Enhancing Enterprise Competitiveness and SME Linkages : Lessons from International and National Experience - World Bank Group (World Bank, Washington, DC, 2018)
Boosting productivity growth, especially that of the domestic private sector, is a key priority of Vietnam. The country has been successful in attracting foreign direct investment (FDI) and entering global value chains (GVCs). Most local firms, however, are small and only serve the domestic markets. FDI has brought enormous gains to Vietnam in terms of growth, exports and jobs, but has been less stellar in developing linkages with the domestic economy. This is reflected in low domestic value addition and a weak supplier base in Vietnam. With increasing global competition, and its ambition to move up the value chain, Vietnam has a unique window of opportunity to exploit its current position in GVCs.